EVALUASI PERDA PROVINSI JAWA TENGAH TENTANG BAHASA, SASTRA DAN AKSARA JAWA - Soewanto Adhi (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Regional Autonomy provide a wider space and greater responsibility for local governments to preserve and develop culture. Central Java province government has had a Provincial Regulation on Language, Literature, and Java script since 2012 that is Regulation Number 9 of 2012 on Language, Literature, and Java script. In that regulation obligations of local governments and communities at the same strategies in order to preserve and develop the language, literature and Java script were arranged. This research used qualitative approach to evaluate the regulation and how it has been implemented so far. The results showed that the regulation has met the criteria of good legislation. The criteria are the clarity of purpose, Institutional or proper forming organization, the suitability between type and material content, can be implemented, results effectiveness and usefulness, formulation clarity and openness. The strategy that has not been implemented was to popularize the usage of the Indonesian language along with Java script for naming public places and buildings.